(untitled) (Stato, Chiese e pluralismo confessionale, 2015)
Article peer reviewed SOMMARIO: 1. Introduction - 2. Pre-revolutionary period - 3. The Soviet period -4. Modern stage - 5. Conclusion. Abstract: The article examines main stages of formation of the secular state in the Russian Federation. The author provides historical and legal overview of the development of secularism in Russia in the period starting from 1701 to the present days.